2016
DOI: 10.1515/cclm-2015-0281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum albumin level changes in acute ischemic stroke: the role of biological and analytical variation

Abstract: This study shows that sAlb levels might change during the first days after an acute IS, but these changes although statistically significant are not clinically significant if we take into account the analytical and biological variation of sAlb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Besides, malnutrition during hospitalization might be the most probable explanation for the continuous decreasing albumin level during the first 7 days. A decreasing trend in Alb after AIS was also reported by Makris et al 29 …”
Section: Discussionsupporting
confidence: 82%
“…Besides, malnutrition during hospitalization might be the most probable explanation for the continuous decreasing albumin level during the first 7 days. A decreasing trend in Alb after AIS was also reported by Makris et al 29 …”
Section: Discussionsupporting
confidence: 82%
“…A previous study found that serum albumin levels might change during the first days after stroke, especially in patients with poor outcome. 39 Therefore, our data may partially magnify the negative relationship between hypoalbuminemia and outcome. Third, serum albumin measurement of sub-centres was not uniform.…”
Section: Open Accessmentioning
confidence: 83%
“…Hypoalbuminemia and hypoproteinemia seen in the gentamicin-untreated group could be attributed to reduced albumin synthesis by the liver and to the leaking of albumin into the urine. Acute kidney injury has been viewed as an acute systemic disease with significant effects on other organs such as the liver in a process named organ crosstalk (Lane et al, 2013 andMakris &Spanou, 2016). Some lipid abnormalities are also caused by changes in liver metabolism.…”
Section: Discussionmentioning
confidence: 99%